1993
DOI: 10.1093/clinids/17.supplement_2.s494
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Susceptibility Testing of Yeasts: A Brief Overview

Abstract: Antifungal susceptibility testing of yeasts has lacked reproducibility because of the absence of universally accepted guidelines. The major sources of variation in susceptibility testing have been attributed to the choice of medium and pH, inoculum preparation and size, incubation temperature and time, and end-point criteria. These parameters have been addressed by the National Committee for Clinical Laboratory Standards (NCCLS) Subcommittee on Antifungal Susceptibility Testing, and proposed guidelines have re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…Investigating the patterns of resistance by antifungal susceptibility testing is one of the phenotypic methods and its role in epidemiological surveillance is limited 1 . But it is important to determine susceptibility patterns and resistance rates of the Candida isolates recovered from ICU patients as yeast species show discrepancies concerning virulence and resistance to antifungal agents 14–17 . Results of our antifungal susceptibility testing showed that MIC values of amphotericin B and fluconazole against the C. albicans , C. tropicalis , and C. glabrata isolates varied.…”
Section: Discussionmentioning
confidence: 98%
“…Investigating the patterns of resistance by antifungal susceptibility testing is one of the phenotypic methods and its role in epidemiological surveillance is limited 1 . But it is important to determine susceptibility patterns and resistance rates of the Candida isolates recovered from ICU patients as yeast species show discrepancies concerning virulence and resistance to antifungal agents 14–17 . Results of our antifungal susceptibility testing showed that MIC values of amphotericin B and fluconazole against the C. albicans , C. tropicalis , and C. glabrata isolates varied.…”
Section: Discussionmentioning
confidence: 98%
“…However, its antifungal activity is basically restricted to the genus Candida, C. neoformans isolates and dermatophytes. It is important to note that fluconazole has no antimycotic activity against Aspergillus spp and Fusarium spp, the agents which usually cause keratitis (15,25) . Regarding fluconazole MIC, we obtained a large variation of values against the tested ocular pathogens, including one C. albicans strain that exhibited a MIC value higher than the MIC-90 for the 8 tested samples (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…However, the capsule formulation available shows bioavailability limitations affecting its serum levels and tissular distribution. Therefore, in spite of its high tolerability and broad spectrum, its clinical ophthalmologic use is restricted (25)(26) . In the present study, MIC values for itraconazole were quite lower than those recorded for fluconazole when we evaluated Candida spp specimens.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that trailing growth is mainly associated to azoles, these drugs being fungistatic rather than fungicidal [8, 13]. In this context, the lack of a clear‐cut endpoint complicates the interpretation of the test.…”
Section: Discussionmentioning
confidence: 99%